بیوع میں تعقل پسندانہ رجحانات اور ان کے اسباب: فقہی و فکری تجزیاتی مطالعہ: Rationalist Trends and Their Causes in Sales: A Jurisprudential and Intellectual Analytical Study (Al-Aasar, 2025)
The discourse surrounding Islamic commercial transactions (buyu‘at) has increasingly been shaped by rationalist trends that prioritize intellectual reasoning over traditional exegesis. Rationalist scholars, in their attempt to validate these perspectives, often employ philosophical argumentation, contextual reinterpretation, and selective engagement with Qur’anic and Prophetic texts. While presented under the guise of modern hermeneutics, such interpretations are frequently marked by subjective tendencies and individualistic arbitrariness. The underlying causes of these personalized readings stem from the pressures of modern socio-economic realities, the influence of global intellectual paradigms, and the conscious prioritization of human reason above transmitted tradition. Addressing these challenges requires rigorous scholarly critique grounded in established principles of Islamic jurisprudence (usul al-fiqh) and hermeneutical discipline. Failure to academically and methodically counterbalance these arbitrary interpretations risks profound consequences, including the erosion of juristic authority, the distortion of core legal principles, and the proliferation of intellectual and moral disorder within Muslim societies.